In-Situ Growth of Two-Dimensional Gold Nanoclusters on Glass Surface for On-Site Surface-Enhanced Raman Spectroscopic Detection - Tang, Bin; Han, Fangyuan; Zhu, Liping; Luo, Zongchang; Wang, Jialin; Xu, Zhaodan; Wu, Renneng (Frontiers in Physics, 2021)
Analytical science has always been calling for simple, fast and ultra-sensitive methods to sense molecules of interest. Surface-Enhanced Raman Spectroscopy (SERS) has drawn much attention as a convenient tool for molecular fingerprint characterization. In addition to sample preparation, the key point of sensitive SERS detection is the preparation of highly reproducible and sensitive SERS substrates. In this paper, 2D gold nanoclusters are grown on surfaces of glass slips using an in-situ cyclic growth method in aqueous solutions to prepare high-quality SERS substrates, whose surface morphology can be effectively modulated by adjusting a few parameters during preparation. Substrates prepared with optimized parameters exhibit high SERS activity, uniform response, and good batch-to-batch reproducibility. Due to their strong absorption in the near-infrared range, the substrates can be combined with a portable Raman spectrometer with 785 nm excitation wavelength to detect traces of dibenzyl disulfide (DBDS), a major source of corrosive sulfur in mineral insulating oil. A detection limit lower than 1 mg/L can be achieved with the aid of a simple sample pretreatment method, representing a promising on-site insulating oil analysis method for electric power industry.